The Zimbabwe Human Rights Commission and police oversight in Zimbabwe: prospects and challenges - Mugari, Ishmael (Acta criminologica, 2019)
Police officers wield wide discretionary powers, which, amongst others, include; the power to arrest, detain and search. All too often, police organisations have had to content with allegations of abuse of these discretionary powers. The abuse of power mainly manifests through serious violations of citizens’ fundamental rights. Various measures are available to curb violations of citizens’ rights by the police, and include: parliamentary oversight; oversight by the courts; oversight by the media and civic society; and oversight by the human rights commission. This paper explores the effectiveness of the Zimbabwe Human Rights Commission (ZHRC) as a police accountability institution, and evaluates the regulatory framework for the operation of this key institution. Purposive sampling was utilised to gather data from a sample of 126 participants from various institutions of accountability, such as the Court, The Zimbabwe Human Rights Commission, Parliament of Zimbabwe, and media and non-governmental organisations. In the absence of an independent body to solely deal with police misconduct in Zimbabwe, it was found that participants trust the Zimbabwe Human Rights Commission to handle human rights-related cases of police misconduct. Whilst the nation has taken an important step to establish the Zimbabwe Human Rights Commission through constitutional provision and promulgation of an enabling statute, the institution has encountered several obstacles. In this regard, limited investigative powers, limited funding and centralisation of Zimbabwe Human Rights Commission offices are highlighted as factors, which impede the efficiency of Zimbabwe Human Rights Commission.